2006
DOI: 10.1111/j.0014-3820.2006.tb01845.x
|View full text |Cite
|
Sign up to set email alerts
|

Within-Population Variation in Cytoplasmic Genes Affects Female Life Span and Aging in Drosophila Melanogaster

Abstract: Abstract. It has been suggested that mitochondrial DNA (mtDNA) may play an important role in aging. Yet, few empirical studies have tested this hypothesis, partly because the degree of sequence polymorphism in mtDNA is assumed to be low. However, low sequence variation may not necessarily translate into low phenotypic variation. Here, we report an experiment that tests whether there is within-population variation in cytoplasmic genes for female longevity and senescence. To achieve this, we randomly selected 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 44 publications
(33 reference statements)
5
41
2
Order By: Relevance
“…A number of recent experimental studies have shown that alternative naturally occurring mitochondrial DNA (mtDNA) haplotypes encode for alternative phenotypes: mtDNA variation has been shown to be associated with, for example, differences in mitochondrial bioenergetics [1, 2], metabolic rate [3], behavior [4], growth rate [5], life span [6] and fitness [79] and these effects are often expressed as epistatic interactions with the nuclear genome [10, 11]. Apart from casting doubt on the dated assumption that mtDNA variation is neutral [12, 13], these findings also raises the important question of what balancing processes act to maintain within-population variation in this haploid, maternally inherited and non-recombining genome in the face of selection where overdominance cannot occur [14].…”
Section: Resultsmentioning
confidence: 99%
“…A number of recent experimental studies have shown that alternative naturally occurring mitochondrial DNA (mtDNA) haplotypes encode for alternative phenotypes: mtDNA variation has been shown to be associated with, for example, differences in mitochondrial bioenergetics [1, 2], metabolic rate [3], behavior [4], growth rate [5], life span [6] and fitness [79] and these effects are often expressed as epistatic interactions with the nuclear genome [10, 11]. Apart from casting doubt on the dated assumption that mtDNA variation is neutral [12, 13], these findings also raises the important question of what balancing processes act to maintain within-population variation in this haploid, maternally inherited and non-recombining genome in the face of selection where overdominance cannot occur [14].…”
Section: Resultsmentioning
confidence: 99%
“…Mitonuclear mismatch also produced sterile hybrids between the yeast species Saccharomyces cerevisiae and S. bayanus (Lee et al 2008), and hybrid breakdown between species of Nasonia wasps , Drosophila (Sackton et al 2003), centrarchid fishes (Bolnick et al 2008) and several plant species (Bomblies 2010 and references therein). Studies on Drosophila that have manipulated nuclear and mitochondrial genetic variation have found that mitonuclear epistasis is an important force in shaping longevity variation (James and Ballard 2003;Rand et al 2006;Maklakov et al 2006;Ballard et al 2007;Clancy 2008;Dowling et al 2009). Observations that naturally occurring levels of mitochondrial genetic variation could produce substantial variation in longevity shed new light on the mitochondrial theory of ageing (reviewed in Morrow and Tanguay 2008;Bratic and Trifunovic 2010;Kirkwood and Kowald 2012).…”
Section: Introductionmentioning
confidence: 99%
“…, 2005). Second, several studies have revealed associations between naturally occurring levels of mitochondrial or cytoplasmic genetic variation and patterns of ageing in Drosophila (James & Ballard, 2003; Maklakov et al. , 2006; Rand et al.…”
Section: Introductionmentioning
confidence: 99%